PNBE do professor : usos e desusos - Brandão, Claudia Leite (2016)
This Master’s thesis is linked to the researchers group ALFALE, Grupo de Pesquisa Alfabetização e Letramento Escolar, a project developed by the Master Degree Program of Federal University of Mato Grosso, in Rondonópolis city. This research investigates the public policies concerning to the incentive to professional articulated reading with the teacher’s PNBE. The aim of this research is to comprehend how the books which compose the PNBE (2010, 2013) are acquired, distributed, provided and used by primary school teachers in four public elementary schools of a city called Primavera do Leste, in Mato Grosso. The findings presented here are the result of a quantitative and qualitative methodological approach based on case study. The thesis uses questionnaires, systematized observation and document analysis as data collection instrument. The researcher’s participants were the principals, the coordinators, the teachers and the people responsible for the library of these four public elementary schools. The investigation revealed that the PNBE’s books were successfully delivered, but there were still books inside sealed boxes. This fact demonstrates that the PNBE’s material is not being used according to the goals and expectations of the program. One of the reasons pointed for the questionnaires’ information for this occurrence is the lack of knowledge about the PNBE by the people responsible for the library, the teachers, the coordinators and the principals. The thesis points out the need of spreading more information about the program, since the acquisition of the material until its implementation.